2017
DOI: 10.1080/13854046.2017.1384063
|View full text |Cite
|
Sign up to set email alerts
|

Impaired eye contact in theFMR1premutation is not associated with social anxiety or the broad autism phenotype

Abstract: This study supports reduced eye contact as a phenotypic feature of the FMR1 premutation, which presents independent of social anxiety and the BAP. These findings contribute to a growing understanding of the neuropsychological phenotype of the FMR1 premutation, which has public health implications given that >1 million individuals in the United States carry this genetic abnormality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 84 publications
0
7
0
Order By: Relevance
“…Thus, filled pauses can serve as pragmatic markers, and some emerging evidence suggest that their occurrence is correlated with measures of autism symptom severity ( Irvine et al, 2016 ). Pragmatic language difficulties and features of the broad autism phenotype have been documented in women with the FMR1 premutation in a number of prior reports ( Losh et al, 2012 ; Schneider et al, 2016 ; Klusek et al, 2017b , c , 2018 ). Follow-up studies are needed to explore the possibility that the filled pause disfluencies observed in the present study marked pragmatic, rather than executive, processes.…”
Section: Discussionmentioning
confidence: 96%
“…Thus, filled pauses can serve as pragmatic markers, and some emerging evidence suggest that their occurrence is correlated with measures of autism symptom severity ( Irvine et al, 2016 ). Pragmatic language difficulties and features of the broad autism phenotype have been documented in women with the FMR1 premutation in a number of prior reports ( Losh et al, 2012 ; Schneider et al, 2016 ; Klusek et al, 2017b , c , 2018 ). Follow-up studies are needed to explore the possibility that the filled pause disfluencies observed in the present study marked pragmatic, rather than executive, processes.…”
Section: Discussionmentioning
confidence: 96%
“…A variety of social difficulties have been documented as part of the FMR1 premutation phenotype, such as atypical use of eye gaze, elevated broad autism phenotype traits, and ASD occurring in about 5% of females with the premutation (Clifford et al 2007; Klusek et al 2017b, c; Losh et al 2012; Schneider et al 2016). Social deficits in this group extend to the domain of pragmatics.…”
Section: The Fmr1 Premutationmentioning
confidence: 99%
“…Premutation status is approximately twice as likely to occur in females than males, highlighting the critical importance in better understanding neuropsychiatric features in female PMCs ( Hunter et al, 2014 ). Previous studies have documented both intact and impaired executive function, social processing, and psychiatric features of depression and anxiety in female PMCs without FXTAS relative to age- and sex-matched typically-developing controls (TDCs) ( Bennetto et al, 2001 ; Hessl et al, 2001 ; Loesch et al, 2003 ; Ennis et al, 2006 ; Allen et al, 2007 ; Hunter et al, 2008a , b ; Rodriguez-Revenga et al, 2008 ; Roberts et al, 2009b , 2016 ; Seltzer et al, 2012 ; Yang et al, 2013 ; Kraan et al, 2014 ; Mailick et al, 2014 ; Wheeler et al, 2014 ; Shelton et al, 2016 ; Klusek et al, 2018b ; Nayar et al, 2019 ; Winston et al, 2020 ). Severity of executive dysfunction ( Hunter et al, 2008b ; Goodrich-Hunsaker et al, 2011a , b ; Klusek et al, 2020 ), psychiatric symptoms ( Allen et al, 2007 ; Roberts et al, 2009a ; Seltzer et al, 2012 ), and social-communication differences ( Schneider et al, 2016 ; Klusek et al, 2018a ; Maltman et al, 2021 ) have linear and curvilinear associations with increased CGG repeat count in female PMCs.…”
Section: Introductionmentioning
confidence: 99%